D12 Faulty linear and back-splicing in Huntington's disease: novel players in the pathologic process hint at innovative RNA biomarkers. (12th September 2022) - Pellegrini, Miguel; Ayyildiz, Dilara; Bergonzoni, Guendalina; Monziani, Alan; Tripathi, Takshashila; Döring, Jessica; Cardamone, Giulia; Kerschbamer, Emanuela; Di Leva, Francesca; Perrone, F; Abruzzese, MP; Busi, LC; et al.
Abstract : Alternative Splicing (AS) is crucial for generating protein-coding isoforms and circular RNAs (circRNAs), stable non-coding RNA's produced by circularization of exons through the back-splicing process. Here, taking advantage of Htt CAG knock-in mouse in vitro and in vivo models, we demonstrate a strong correlation between Htt CAG repeat length and increased aberrant linear AS, specifically affecting neural progenitors and, in vivo, the striatum prior to overt behavioral phenotypes stages. Remarkably, expanded Htt CAG repeats reflect on a previously neglected, global impairment of back-splicing, leading to decreased circular RNAs production in neural progenitors. Though the mechanisms of this dysregulation remain uncertain, our study unveils transcriptionally altered micro-RNAs, possibly impacting the expression of RNA-binding proteins, primarily in neural cells. We suggest that this unbalanced expression of linear and circular RNAs might result in altered neural fitness and contribute to disease. With the development of new therapies entering clinical trials for HD, there is an increasing need to develop and validate biomarkers in accessible biofluids (such as blood) to follow disease progression and predict treatment's outcome. Here, we detect and characterize circRNAs in peripheral blood of a cohort of gender and age matched healthy and HD individuals at different stages of the disease. We investigate their potential use as biomarkers by evaluating their correlation with disease progression and the length of the CAG repeat. Interestingly, 35 circRNAs, whose expression significantly increases in HD, possibly identify new disease biomarkers to assess the pathogenic process and the pharmacologic responses to therapeutic intervention.